The Reasons for EFL University Students Employ Hedges during Their Speaking Class - Imran Trista Udin; Zulkhaeriyah; Fiviyanti Hasim (Hasanuddin University, 2022)
Communication is important in language schools because it connects the meaning of a person's thoughts. As a result, as foreign language learners, students must grasp how to engage effectively with other students. In this regard, the researcher believed it was critical to explore English Foreign Language (EFL) university students' communication styles during their speaking class, which included hedges. The research aims were to discover the sorts of hedges used by EFL university students during their speaking class in an academic context, as well as the reasons why EFL university students used hedges during their speaking class. This study was conducted at Politeknik LP3I Makassar and it was focused on the students in the first semester in subject Basic Speaking with the total participants were 23 students of one class. The method used was descriptive qualitative method. There were 6 recordings in the interview sections the theory from Riekkinen and Svarova (2009) was used to analyze the data gained. After transcribing and analyzing the data, the results showed that the students employ hedges for some reasons. The first reason was to express a personal evaluation or a suggestion to put into practice for a current situation, the second reason was markers of vagueness that will enable students to express uncertainty, the third reason gained in interview section was to apply a need in a situational context such as request, seek permission, and giving advice, and the last reason was to apply politeness in requesting the attention of the hearer.